Monitoring and assessment of tree health condition in Kaunas city environment - Stravinskienė, Vida (Journal of Environmental Engineering and Landscape Management, 2010)
The paper presents the results of monitoring the changes of selected parameters in different tree species carried out on 69 observation plots in the city of Kaunas in 2002 and in 2008. The morphological parameters (crown defoliation, foliage discolouration, fruiting rate and amount of dry branches) of 769 sampled trees were evaluated. The investigation indicated that trees growing closer to streets had greater defoliation compared to trees growing in city wooded areas or parks far from the streets. The largest average crown defoliation was observed for Aesculus hippocastanum L. – 45.3±2.5%, Tilia cordata Mill. – 29.3±3.9% and Acer negundo L. – 28.2±3.1%. The main reason of large crown defoliation and worse health condition of Aesculus hippocastanumwas air pollution and the cankerous impact of Cameraria ohridella Deschka & Dimic. It is established that large tree foliage dechromation is not widespread in the city of Kaunas. The comparison of monitoring data of 2008 and 2002 indicated the trend of improvement in the health condition of all the tree species, except Aesculus hippocastanum L. The differences in the morphological parameters for the sampled trees in different city regions were estimated. Using an ArcGIS program a map was created with 5 zones for crown defoliation in trees for the city of Kaunas: (defoliation ≤15%) a very favourable zone; (defoliation 16–25%) a favourable zone; (defoliation 26–35%) a moderately favourable zone; (defoliation 36–45%) an unfavourable zone; (defoliation >45%) a very unfavourable for tree growth zone. These zones indicated the degree of suitability of the city environment to tree growth.Article in Lithuanian.Medžių būklės stebėsena ir vertinimas Kauno miesto aplinkojeSantrauka. Analizuojami 2002 ir 2008 metais Kaune atliktos medžių miesto gatvių želdiniuose, skveruose, parkuose ir miško parkuose būklės stebėsenos ir vertinimo rezultatai. 69‐iuose Kauno aplinkos stebėsenos objektuose buvo įvertinta 769 apskaitos medžių būklė pagal indikacinius morfologinius rodiklius (lajų defoliaciją, lapijos arba spyglių dechromaciją, derėjimą ir sausų šakų kiekį ląjoje). Didžiausia vidutinė lajų defoliacija nustatyta paprastųjų kaštonų (Aesculus hippocastanum L.) – 45,3±2,5 %, mažalapių liepų (Tilia cordata Mill.) – 29,3±3,9 % ir uosialapių klevų (Acer negundo L.) – 28,2±3,1 %. Ypač didelės paprastųjų kaštonų lajų defoliacijos pagrindinė priežastis – ne oro tarša, o keršosios kaštoninės kandelės (Cameraria ohridella Deschka & Dimic) pažeidimai. Apskaitos medžių dechromacija palyginti nedidelė. Palyginus 2008 ir 2002 metu medžių būklės stebėsenos duomenis, akivaizdus medžių, išskyrus paprastuosius kaštonus (Aesculus hippocastanum L.), būkles pagerejimas. Nustatyti medžių morfologinių rodiklių skirtumai miesto mikrorajonuose. Taikant ArcGIS programą atliktas miesto teritorijos zonavimas, pagal vidutinę medžių lajų defoliacija išskiriant 5 aplinkos būkles zonas, indikuojančias aplinkos palankumą medžiams augti: medžiams augti labai palanki (lajų defoliacija ≤15 %); palanki (16–25 %); vidutiniškai palanki (26–35 %); nepalanki (36–45 %) ir labai nepalanki (defoliacija >45 %).Reikšminiai žodžiai: miesto medžių būklė, stebėsena, morfologiniai rodikliai, tarša, miesto zonos.Mониторинги оценка состояния деревьев в окружающей среде г. КаунасаРезюме. Представлены результаты мониторинга и оценки состояния деревьев, произрастающих в парках, городских парках и вблизи улиц г. Каунаса. Исследования проведены в 2002 и 2008 гг. на 69 участках мониторинга городской окружающей среды. Определено состояние 769 учетных деревьев по их морфологическим показателям (дефолиации, дехромации крон, уровням плодоношения и количеству сухих ветвей). Основным индикатором состояния деревьев и их среды послужила дефолиация крон. Установлено, что деревья, произрастающие вблизи улиц, находятся в наихудшем состоянии по сравнению с растущими в отдалении от улиц. По средней дефолиации крон в наихудшем состоянии находятся Aesculus hippocastanum L. (дефолиация 45,3±2,5%), Tilia cordata Mill. (29,3±3,9%) и Acer negundo L. (28,2±3,1%). Основной причиной большой дефолиации крон и плохого состояния Aesculus hippocastanum является загрязнение воздуха и повреждение листьев, причиненные Cameraria ohridella Deschka & Dimic. Установлена сравнительно небольшая дехромация учетных деревьев. Определено достоверное улучшение состояния учетных деревьев (за исключением Aesculus hippocastanum) в 2008 г. по сравнению с данными мониторинга 2002 г. Установлены различия морфологических показателей учетных деревьев, произрастающих в различных районах города. С применением программы ArcGIS по данным средней дефолиации крон учетных деревьев выделено 5 зон города: очень благоприятная (дефолиация крон учетных деревьев ≤15%), благоприятная (16–25%), средне благоприятная (26–35%), неблагоприятная (36–45%) и очень неблагоприятная (дефолиация крон >45%).Ключевые слова: городские деревья, мониторинг, оценка состояния, морфологические показатели, загрязнение воздуха, зоны города.First Publish Online: 10 Feb 2011